(untitled) (Research, Society and Development, 2021)
Alternative management practices are necessary to minimize the need for mineral fertilizers in crop systems with non-leguminous crops. The levels of fertilization used, especially with the primary macronutrients NPK, generally influence the growth rate and the development of corn, with positive effects on the production of the crop. This study aimed to evaluate the effect of fertilizer doses and sources of mineral and organomineral formulations on the growth, development and reading of SPAD of corn plants. The experiment was carried out in plastic pots, arranged in the open, filled with 25 L of soil, collected from the 0 to 0.20 m layer of a dystrophic Red Latosol in the Cerrado, at the Experimental Farm of the Federal Goiano Institute, Rio Verde Campus - GO. The experimental design used was randomized blocks in a 5x2 factorial scheme, with four replications, consisting of five doses of formulated NPK 04-14-08 (0, 150, 300, 450, 600 kg ha-1 of the product, equivalent to pot) ) and two sources of mineral and organomineral fertilizers from the formulation, 04-14-08. In the plants, evaluations of the agronomic characteristics were carried out, every fifteen days (30, 45, 65, 75 days after emergence), of plant height, stem diameter, number of leaves, SPAD reading and leaf area. The dose of 600 kg ha-1 of the formulation 04-14-08 provides the best development of stem diameter and plant height. The organomineral source provides a higher corn plant height, number of leaves and leaf area. Organomineral fertilizer is efficient to ensure the growth and development of corn.